1999
DOI: 10.1002/(sici)1521-3935(19990501)200:5<1068::aid-macp1068>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the diallyldimethylammonium chloride (DADMAC) polymers architectures: PEG/DADMAC blocks and partially quaternarized polymers

Abstract: New DADMAC-based macromolecular architectures have been prepared, varying the permanent charge distribution in the polycation structure. DADMAC and PEG-containing block copolymers with (AB) n and ABCBA structures were synthesized via condensation together with thermal and redox radical polymerization. Polymers with a randomly reduced charge density were, on the other hand, obtained via polymer-analogous reactions based on the dequaternarization of the ammonium groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The peak at δ 182.2 ppm confirms the presence of amide carbonyl carbons (g). A broad peak at δ 27.9 ppm is allocated to methylene carbon (d), while the low intensity unresolved broad peak at δ 40.9 ppm is assigned to methine carbon (c), which is following the sequence and values reported by various authors 35–37. The methylene on carbon (b), α‐carbon to DADMAC nitrogen which is buried under the complex structure of guar gum, can be assigned to the unresolved but sharp peak at δ 71.1 ppm which is consistent with literature values 34, 38, 39…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The peak at δ 182.2 ppm confirms the presence of amide carbonyl carbons (g). A broad peak at δ 27.9 ppm is allocated to methylene carbon (d), while the low intensity unresolved broad peak at δ 40.9 ppm is assigned to methine carbon (c), which is following the sequence and values reported by various authors 35–37. The methylene on carbon (b), α‐carbon to DADMAC nitrogen which is buried under the complex structure of guar gum, can be assigned to the unresolved but sharp peak at δ 71.1 ppm which is consistent with literature values 34, 38, 39…”
Section: Resultssupporting
confidence: 87%
“…This assignment of protons signals of the grafted chain is in line with the literature values 33. Guar gum signals could not be identified clearly in the complex spectrum; however, the sequence of signals and their presence is very similar to what is reported in the literature 2, 35. Crescenzi et al2 reported that the last peak in the 1 H‐NMR of guar gum comes at δ 5.02 ppm and nothing was reported further downfield.…”
Section: Resultssupporting
confidence: 77%
“…The degree of grafting was a strong function of the radiation dose, dose rate, and polyelectrolyte concentration. New DADMAC and polyethylene glycol containing block copolymers by condensation, together with thermal and redox radical techniques, were obtained 32. One advantage is the randomly reduced charge on the polymer chain.…”
Section: Current Status Of the Fieldmentioning
confidence: 99%
“…A wide range of polymer-clay composite has been produced and used for water treatment (Sebastian, et al, 2014;Gupta, et al, 2016), dye adsorption (El Haddad, et al, 2012; Patil and Shrivastava, 2015) etc. The synthesis of ionic copolymers has been gaining significant interest among researchers (Tirelli and Hunkeler, 1999). Diallyldimethylammonium chloride (DADMAC) is one of the water soluble cationic monomer that has wide range of applications in water treatment, medicine, electrical switches, etc.…”
Section: Introductionmentioning
confidence: 99%